Current and future trends and issues facing technology education in Finland—Taking part in an international Delphi study - Niiranen, Sonja; Ikonen, Pasi; Rissanen, Timo; Rasinen, Aki (Australasian Journal of Technology Education, 2022)
This study is part of an international research collaboration aimed at identifying current and future trends and issues in technology education in Belgium, Finland, Japan and the USA. The three-round Delphi method was utilised to solicit information from technology education stakeholders in Finland from November 2019 to April 2020. The panel of experts (N=31) comprised technology education teacher educators, researchers and experts of the national LUMA (STEM) 2020 programme and technology education developers. During the Delphi process both quantitative and qualitative approaches were utilized in gathering information and analysing the findings. In this article the focus is on comparing the most relevant trends and issues identified by craft and technology education professionals after Round 3. The data were analysed using qualitative content analysis. These findings reveal the unclear role of technology education in Finland and the need for a clear definition for it on the national curriculum level.